New perspectives on foreign aid and economic development - Arvin, B. Mak, 1959- (Praeger, 2002)
The success or failure of economic assistance programs is a shared responsibility of recipient countries and donors. The negative attitude about aid prevalent today underscores a perception the aid has failed. Critics often blame corrupt regimes, weak governments, or poor economic policies. However, the poor track record of aid is also due to donors' inability to allocate limited funds effectively and poor coordination of their aid efforts. Declining aid budgets have led to fundamental questioning of foreign aid's allocation and utility, while the apparent ineffectiveness of aid had shrunk aid budgets and turned public opinion against providing it. This edited collection containing pieces written by leading development specialists evaluates these emerging questions of allocation and efficiency. Development economists, policy makers, and development specialists will benefit from reading this work.